2020
DOI: 10.1038/s41389-020-0203-6
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-378a-5p iS a novel positive regulator of melanoma progression

Abstract: Evaluating the expression levels of miR-378a-5p both in a large melanoma patient cohort from The Cancer Genome Atlas database and in melanoma patients from our Institute, we found that miR-378a-5p is upregulated in metastatic melanoma specimens. miR-378a-5p expression was also increased in melanoma cells resistant to target therapy, and decreased in response to drug treatment. We also demonstrated that overexpression of miR-378a-5p enhances in vitro cell invasion and migration, and facilitates the ability of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…EVs are broadly classified into four subtypes based upon vesicle size: 1) exosomes (30-150 nm), 2) microvesicles (50-1000 nm), 3) large vesicles (>1000 nm) and 4) apoptotic bodies (>1000 nm) (81). As to metastatic melanoma, most studies have assessed the role of miRNAs as predictors of response to targeted therapies in BRAF-mutant patients (82)(83)(84)(85). For example, we have demonstrated that a mini-signature composed of four miRNAs, i.e.…”
Section: Non Coding Rnas (Ncrnas)mentioning
confidence: 99%
“…EVs are broadly classified into four subtypes based upon vesicle size: 1) exosomes (30-150 nm), 2) microvesicles (50-1000 nm), 3) large vesicles (>1000 nm) and 4) apoptotic bodies (>1000 nm) (81). As to metastatic melanoma, most studies have assessed the role of miRNAs as predictors of response to targeted therapies in BRAF-mutant patients (82)(83)(84)(85). For example, we have demonstrated that a mini-signature composed of four miRNAs, i.e.…”
Section: Non Coding Rnas (Ncrnas)mentioning
confidence: 99%
“…Previous studies indicate that gastric cancer stem-like cells are derived from MKN-45- by the expression change of hsa-let-7b-3p ( Salehi et al, 2018 ). Moreover, microRNA-378a-5p increased the expression level in melanoma cells and is a novel positive regulator of melanoma progression ( Tang et al, 2018 ; Tupone et al, 2020 ). The expression of hsa-miR-26a-5p was downregulated in breast cancer tissues and appeared to have a poor prognosis for patients ( Huang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After 72 h, cells were processed as previously reported [20]. For migration and invasion assays, 5 × 10 4 HUVEC were seeded into upper chamber of Transwell (Corning, Costar, New York, USA) or CultreCoat cell invasion chamber (Trevigen, Gaithersburg, MD, USA), respectively processing them after 6 h as previously reported [21]. For tube formation assay, 2.5 × 10 4 HUVEC or 5 × 10 4 lung cancer cells were seeded in duplicates in 24-well culture plates containing polymerized matrigel (BD Bioscience, San Jose, CA, USA) and incubated with CPTH6 for 6 or 18 h, respectively.…”
Section: In Vitro and In Vivo Angiogenic Assays And Immunohistochemistrymentioning
confidence: 99%
“…All procedures involving animals were authorized by the decree n. 26/2014 of the Italian Ministry of Health, authorization n. 787/2015PR-29/07/ 2015. In vivo angiogenesis matrigel assay was performed as previously reported [21]. Tumor vascularization of LCSC136 xenografts after treatment with CPTH6 [17] was evaluated by detecting CD31-positive cells in 5 μm paraffin sections by a streptavidin-biotin enhanced immunoperoxidase technique in an automated autostainer (BondTM Max, Leica BioSystem).…”
Section: In Vitro and In Vivo Angiogenic Assays And Immunohistochemistrymentioning
confidence: 99%